Diagnostic classification, viral sexually transmitted infections and discourses of femininity: limits of normalisation to erase stigma. Issue 2 (14th February 2012) - Cook, Catherine
<x xml:space="preserve">Abstract</x> Clinicians in the field of women's sexual health typically classify the two most common viral sexually transmitted infections (STIs), the human papilloma virus and the herpes simplex virus, as relatively innocuous infections. Teaching interventions include 'normalising' adult sexual activity and the epidemiological ordinariness of infection. Normalising is intended to disarm the potential stigma of the diagnosis. In this study, in‐depth email interviews were conducted with 26 women with a viral STI diagnosis and 12 sexual health clinicians. Data were analysed thematically using a feminist, poststructuralist approach. Normalising is contextualised as an example of the workings of western philosophical thought whereby dualistic classifications privilege certain terms and subordinate other terms. In this instance, the relative medical normalcy of viral STIs is given primacy compared to the social abnormality experienced by women. Although these viral STIs infect women and men, this research concentrates on women's learning about viral STIs. For women, beliefs about femininity, sexuality, health, morality and responsibility influence effects of a viral STI diagnosis. These discourses are clinically significant because beliefs that specifically link to ideas about how to be a woman are overlooked when clinicians devise educational interventions.